Sanitary Surveillance of natural latex male condoms commercialized in Rio de Janeiro, Brazil: analysis of volumetric capacity and burst pressure - Janete Teixeira Duarte; Antonio Eugenio Castro Cardoso de Almeida; Shirley de Mello Pereira Abrantes (Fundação Oswaldo Cruz (FIOCRUZ), 2014)
Objective: The increased importance of using condoms to protect men and women from sexually transmitted diseases and HIV infection has sensitized health authorities to condom quality. However, the resolution for product certification is also used for sanitary evalua-tion. Although the certification process evaluates in detail manufacturing the production and final product, it does not address marketing in establishments such as pharmacies, drugstores, and supermarkets - a typical issue considered for Sanitary Surveillance. Quali-ty control of male condoms involves the important insufflation test, which evaluates resis-tance by determining volumetric capacity and bursting pressure. Method: We evaluated 20 brands of male condoms, domestic and imported, from eight manufacturers, marketed in Rio de Janeiro, Brazil. We tested 200 units per brand. Results: All brands met the criteria established in the Brazilian National Health Oversight Agency Resolution no. RDC 62/2008, which allows up to eight nonconforming units. However, nonconforming units were identi-fied in 12 of the brands tested. Conclusion: From the perspective of Sanitary Surveillance, even a single nonconforming unit has serious implications for public health.